Characterization of a Discontinuous Neutralizing Epitope on Glycoprotein B of Human Cytomegalovirus - Spindler, Nadja (American Society for Microbiology, 2013)
Human cytomegalovirus (HCMV) is a ubiquitously distributed pathogen that causes severe disease in immunosuppressed patients and newborn infants infected in utero. The viral envelope glycoprotein B (gB) is an attractive molecule for active vaccination and passive immunoprophylaxis and therapy. Using human monoclonal antibodies (MAbs), we have recently identified antigenic region 4 (AD-4) on gB as an important target for neutralizing antibodies. AD-4 is formed by a discontinuous sequence comprising amino acids 121 to 132 and 344 to 438 of gB of HCMV strain AD169. To map epitopes for human antibodies on this protein domain, we used a three-dimensional (3D) model of HCMV gB to identify surface-exposed amino acids on AD-4 and selected juxtaposed residues for alanine scans. A tyrosine (Y) at position 364 and a lysine (K) at position 379 (the YK epitope), which are immediate neighbors on the AD-4 surface, were found to be essential for binding of the human MAbs. Recognition of AD-4 by sera from HCMV-infected individuals also was largely dependent on these two residues, indicating a general importance for the antibody response against AD-4. A panel of AD-4 recombinant viruses harboring mutations at the crucial antibody binding sites was generated. The viruses showed significantly reduced susceptibility to neutralization by AD-4-specific MAbs or polyclonal AD-4-specific antibodies, indicating that the YK epitope is dominant for the AD-4-specific neutralizing antibody response during infection. To our knowledge, this is the first molecular identification of a functional discontinuous epitope on HCMV gB. Induction of antibodies specific for this epitope may be a desirable goal following vaccination with gB.